Kepemimpinan Kepala Madrasah Dalam Meningkatkan Mutu Sumber Daya Guru - Nurlila, Sintia; Nofrida, Emiliya (Program Studi Pendidikan Guru Madrasah Ibtidaiyyah (PGMI) IAINU Kebeumen, 2023)
Improving the quality of human resources is a must for educational institutions, because teachers are the main key to the success of the teaching and learning process in schools. Quality students are often supported by competent teachers. This study reveals the leadership of madrasa principals in improving the quality of teacher resources. This research uses a qualitative approach with this type of research is descriptive analysis research. Collecting data in this study using interview and observation techniques. Data were analyzed using the Miles and Huberman approach. The results of the study stated that the leadership of the madrasa head in improving the quality of teacher resources was carrying out teacher development activities in the form of involving teachers in training or seminars and encouraging teachers to continue higher education.